Effect of microstructural change on the optical property of Ormosil embedded with organic molecules - Kim, GD; Lee, DA; Kim, JD; Moon, JW; Lee, HM (KLUWER ACADEMIC PUBL, 1997)
An organically modified silicate (Ormosil) for a dye laser was produced with a 90/10 ratio of Tetraethyl orthosilicate and Polydimethyl silanol (TEOS/PDMS) by sol-gel method. The optical properties of a dye incorporated in Ormosil were studied as a function of the amount of catalyst. In the xerogel doped with Rhodamine 6G perchlorate, a dimer peak near 500 nm appeared with increases of HCl amounts. The dimer peak was affected by enlarged pore size of the Ormosil and increased porosity due to the increased HCl concentration. Also, the increase of HCl concentration led to gradually lower transmittance values of the dye host. The dimer peak was identified by measuring optical absorption by ultraviolet/visible spectrophotometer. The changes of pore structure and porosity were investigated by SEM and BET.
Keywords: LASER; DYE; RHODAMINE-6G; BEHAVIOR; PHOTOSTABILITY; FILMS